A Lacanian Theory of Curriculum in Higher Education The Unfinished Symptom - Murillo, Fernando M. (Springer International Publishing, 2018)
This volume presents a distinctively Lacanian psychoanalytic approach to the theorizing, understanding, and critique of curriculum in higher education. In this work, the author presents the main theories of curriculum in the current discourse, develops a notion of critique, and applies it to existing global guidelines for curriculum reform. Relying on the architectonic of the subject as developed across the work of Jacques Lacan-expressed in the registers of the Symbolic, the Imaginary, and the Real-the author provides a new approach to understanding curriculum in terms of the psychic dynamics that explain its workings.